Bridging the Gap: Academic and Social Challenges of First Year Out-of- Town English Students at Mulawarman University - Mukhtasyar, Mukhtasyar Al Hazami; Asih, Yuni Utami; Aridah (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2025)
This study aims to investigate the academic and social challenges faced by new students in the English education, study program at Mulawarman University Who come from outside the city. This study uses a qualitative case study design with four participants who had the lowest GPA in the last semester. Data were collected through Semi-structured interviews and analyzed using thematic analysis. The results of the study show, remained these academic challenges Social Challenges and strategies for overcoming these challenges. Academic challenges include time management in dealing with heavy workloads and difficulties in understanding English-based learning. Social challenges include homesickness, lack of confidence, and difficulties in social adaptation. Despite facing various obstacles. students implemented several strategies, such as asking for help from Friends, joining campus, organizations, and Independent Learning This study emphasizes, the importance of Campus, support systems, in helping new students from outside the region, adapt and succeed academically. And socially These findings can serve as input for lecturers, program administrators and campus officials in designing orientation programs, and students Support Services.